2-micron pulse compression using gas-filled negative curvature hollow-core fiber - Lee, Elizabeth (2019)
Differential-pressured argon-filled negative curvature hollow-core fiber (NC-HCF) with an anomalous dispersion in the mid-infrared was studied for pulse compression. Preliminary simulation results show compression of 2-micron, 1.8-ps, 50 μJ pulse to 110 fs by using a negative-pressure-gradient argon-filled 8.2 m-long NC-HCF at a maximum pressure of 2.65 bar.